Seroprevalence of HBV and HCV Among Whole Blood Donors at a Tertiary Care Research Institute in Northern India - Rubiya Ryhan (Dr. Annil Mahajan, 2023)
Background: Blood transfusion has become a specialized modality of patient management and every year saves millions of lives. However, it is not always safe and may lead to many life-threatening complications amongst which Transfusion Transmitted Infections (TTIs) like HIV, HBV and HCV are most significant and detrimental for the recipients. So, an integrated strategy for blood safety is required for elimination of TTIs and or provision of safe and adequate blood transfusion services to the people. Aim: To assess the sero-prevalence of HBV and HCV infections amongst whole blood donors at tertiary care research Institute. Material and Methods: It is a hospital-based study carried over a period of 7 years from Jan 2015 to Dec 2021. All donor samples were screened for HBV and HCV by ELISA method. Results: Seroprevalence of HBV and HCV was found to be 0.26 % (202/76188) and 0.24 % (185/76188) respectively. Sero-prevalence was higher for HBV as compared to HCV. Conclusion: It is important to continue screening of donated blood with highly sensitive and specific tests and to counsel donors who are reactive to any of the above infections and conduct extensive public awareness programmes to make transfusion of blood and blood components safe.